Short-term treatment of CIDP with efgartigimod: a case series in China - Sun, Chong; Hu, Jianian; Zhao, Yanyin; Zheng, Yongsheng; Meng, Quanhua; Luo, Sushan; Qiao, Kai; Sun, Jian; Lu, Jiahong; Lin, Jie; Zhao, Chongbo (Frontiers in Immunology, 2025)
ObjectiveChronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a type of autoimmune neuropathy with treatment challenges due to the limitations of standard of care therapies. Efgartigimod, a neonatal Fc receptor antagonist, has shown potential in treating antibody-mediated disorders including CIDP (ADHERE study), but real-world studies on the application of efgartigimod in CIDP are still lacking. This study aimed to evaluate the short-term efficacy and safety of efgartigimod in five patients with CIDP in China.MethodsClinical effectiveness was assessed using the Inflammatory Neuropathy Cause and Treatment (INCAT) disability scale, Inflammatory Rasch-built Overall Disability Scale (IRODS), Medical Research Council (MRC) sum score (0–60), grip strength, Neuropathy Impairment Score (NIS), and 3-m Time Up and Go Test (TUG). Safety was evaluated by monitoring adverse events and measuring white blood cell count, serum albumin concentration, and plasma IgG concentration. Peripheral CD4+ T and CD19+ B lymphocytes were measured before and after efgartigimod treatment.ResultsAll five (100%) patients responded to efgartigimod treatment, with four (80%) meeting predefined effectiveness criteria within 8 weeks. The average reduction rate in total IgG was 43%. Adverse events were minimal, with one patient experiencing transient diarrhea, and no aggravation of pre-existing conditions was noted.InterpretationEfgartigimod demonstrates promising efficacy and safety for short-term treatment of CIDP, offering a potential alternative therapy. This study provides valuable evidence from the real-world application of efgartigimod in CIDP, and the results indicate further research is warranted.